2002
DOI: 10.1097/00000658-200206000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and Postoperative Bleeding After Coronary Artery Bypass Grafting

Abstract: ObjectiveTo evaluate the relationship between aspirin ingestion and postoperative bleeding complications, and to test the hypothesis that there is a subset of patients who are aspirin hyperresponders with a proclivity toward platelet dysfunction. Summary Background DataDespite numerous retrospective and prospective analyses, it is still controversial as to whether aspirin ingestion before coronary artery bypass grafting (CABG) is associated with significant postoperative bleeding. MethodsBetween January 1995 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 36 publications
4
56
0
7
Order By: Relevance
“…In the present study, only isolated CABG patients were included which enhanced the robustness of the results. Ferraris and coworkers supported the premise that enhanced platelet inhibition following ASA administration results in bleeding tendency [15]. Our findings suggest a similar phenomenon.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, only isolated CABG patients were included which enhanced the robustness of the results. Ferraris and coworkers supported the premise that enhanced platelet inhibition following ASA administration results in bleeding tendency [15]. Our findings suggest a similar phenomenon.…”
Section: Discussionsupporting
confidence: 87%
“…This can result in diminished bleeding tendency in group of patients with high residual platelet reactivity regardless of APT administered. On the other hand, there is evidence that certain patients have an accentuated response to the usual doses of preoperative aspirin that may result in increased perioperative blood loss requiring PRBC transfusion [15]. Those facts can argue that quantified platelet function can be predictive of transfusion requirements rather than administration of antiplatelet drugs per se.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 1900 patients who had ingested aspirin within 12 hours of coronary artery bypass grafting (CABG) versus 706 who had not, showed a 4.1% increase in the need for red cell transfusion, an increase in the need for platelet and cryoprecipitate transfusion from 2.1% to 4.5% and an increase in the re-operation rate from 2.0% to 3.7%. 34 Studies of patients receiving clopidogrel within a few days of surgery have similarly demonstrated a significant increase in bleeding complications. A prospective study of 470 cardiac surgery patients, 91 of whom had received clopidogrel within 5 days of operation, found an increased relative risk of death, need for intraaortic balloon pump, arrhythmia, re-intubation and stroke in patients who had received clopidogrel, although the number of events was small.…”
Section: Special Issues Related To Surgerymentioning
confidence: 99%
“…Notably, for patients receiving dual antiplatelet therapy preoperatively, the role of aspirin should not be underestimated as it is well known that dual antiplatelet therapy provides more potent aspirin inhibitory effect [6], which in turn enhances the risk of bleeding attributable to aspirin effect [7]. Therefore, it seems reasonable to perform drugs specific platelets function testing using both ADP as well as arachidonic acid induced platelet function agonists.…”
mentioning
confidence: 99%